2021
DOI: 10.7150/jca.48983
|View full text |Cite
|
Sign up to set email alerts
|

LRP1B or TP53 mutations are associated with higher tumor mutational burden and worse survival in hepatocellular carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the most leading causes of cancer-related mortality worldwide. Immune checkpoint inhibitors (ICIs) have been proved to be beneficial for advanced HCC. Tumor mutational burden (TMB) is an important predictor for efficacy of ICIs. However, the genetic landscape of Chinese HCC patients and the association between TMB and frequently mutated genes of HCC remain unclear. Methods: Whole-exome sequencing data of 369 liver tumors from the Cancer Genome Altas (TCGA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 28 publications
5
29
0
Order By: Relevance
“…The somatic mutations of this important tumor suppressor may cause genomic instability and replication stress, which is closely related to tumorigenesis in various cancer types (Baker et al, 1989; Malekzadeh et al, 2019; Nigro et al, 1989; Stracquadanio et al, 2016). LRP1B may play an essential role in the tumorigenesis of NSCLCs, and mutations of this gene are associated with a higher TMB level (Lan et al, 2019; Wang et al, 2021). These factors may be involved in positive selection during tumor evolution and promote the occurrence of HLA‐I LOH.…”
Section: Discussionmentioning
confidence: 99%
“…The somatic mutations of this important tumor suppressor may cause genomic instability and replication stress, which is closely related to tumorigenesis in various cancer types (Baker et al, 1989; Malekzadeh et al, 2019; Nigro et al, 1989; Stracquadanio et al, 2016). LRP1B may play an essential role in the tumorigenesis of NSCLCs, and mutations of this gene are associated with a higher TMB level (Lan et al, 2019; Wang et al, 2021). These factors may be involved in positive selection during tumor evolution and promote the occurrence of HLA‐I LOH.…”
Section: Discussionmentioning
confidence: 99%
“…TMB is usually evaluated using expensive, massive next-generation, or whole-exome sequencing [ 120 ]. Nevertheless, specific single-gene mutation analysis has been presenting as a more accessible way to predict TMB in cancer patients [ 120 ], with LRP1B being one of those genes [ 61 , 120 , 121 ]. In HCC, LRP1B mutation significantly associated with a higher HHLA2 (human endogenous retrovirus-H long terminal repeat-associating protein 2), as well as with TMB, giving new insights into potential targets for immune checkpoint inhibition [ 61 ].…”
Section: Lrp1b Impairment In Cancermentioning
confidence: 99%
“…As a member of the low-density lipoprotein receptor family, LRP1B plays a tremendous function in maintaining lipid homeostasis. A study by Li and colleagues found that LRP1B knockdown caused the decrease in intracellular lipid content, down-regulated expressions of lipid synthesis-related enzymes as well as increased expressions of β-oxidation-related enzymes and enhanced activity of AMPK signaling [ 21 ]. These might offer a potential explanation for LRP1B roles in HCC development.…”
Section: Discussionmentioning
confidence: 99%